The consideration of climate and air hygiene in spatial planning - Schirmer, Hans (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
For an appropriate integration of climate and air hygiene into spatial planning decisions the factors that are relevant in this respect as well as evaluations of the results for the individual planning levels are presented with examples and policy-related recommendations in the new guideline of the German Association of Engineers no. 3787 sheet 9.